Brief Overview on Rabies: A Fatal and Preventable Virus - Abdul Samad; Areesha Naveed; AMM Nurul Alam; Rameen Atique; Ayesha Muazzam; Bushra Anwar; Hafiza Arshi Saeed; Maryam Zahra; Tehreem Rana; Md. Jakir Hossain (Riviera Publishing, 2024)
Rabies is a fatal and acute infection of the brain. The virulence factor of this infection is the Rabies virus, which belongs to the Rhabdoviridae family. It is a zoonotic disease that can be transmitted from animals to humans. The common ways of transferral of Rabies in humans are the transmission of rabies by the bite of a rabid animal and transmission due to saliva and consumption of meat and milk of rabid animals. Some wild animals, e.g., skunks, dogs, raccoons, foxes, and bats, can also transfer rabies in humans, mammals, and other animals. The incubation period of Rabies is at least 2 weeks to a maximum of 6 years, with an average duration of 2 to 3 months. Given its status as a significant zoonotic disease, it is crucial to have an accurate and prompt diagnosis to facilitate early treatment and implement effective measures for prevention and control. This study comprehensively analyzes epidemiology, transmission, etiology, advancements in diagnostics, immunization, therapy methods, and effective prevention and control techniques. The main objective of this study is to brief the threat of rabies and its management along with providing some brief knowledge related to rabies. The web sources (e.g., Google Scholar, Pubmed) were used to collect data regarding Rabies and briefly explained. As a result, it is clear that rabies is a big threat to the whole world so management strategies are required to target and overcome this threat. This study concludes that the Rabies virus can be managed by following the preventive and managemental strategies.